Doing better with "bad kids" - Waddell, Charlotte.; Centre for Health Economics and Policy Analysis (McMaster University, 1998)
Conduct disorder, or persistent antisocial behavior in children and youth, is an important public mental health problem in Canada. There is much research evidence about causal risk factors, prevention and treatment, yet little of the research is incorporated into legislative, administrative or clinical policy decision-making. Decision-making in Hamilton, Ontario is used as a case study to illustrate this research-policy gap. This gap is then explained using a framework for health policy analysis that incorporates values (ideologies, beliefs, interests), institutional structures for decision-making, and research information. Values and institutional structures need to be considered if research evidence is to be disseminated and applied by policy decision-makers to prevent and treat conduct disorder more effectively.
Charlotte Waddell ... [et al.].
Bibliography: p. 23-26.
Keywords: Conduct Disorder; therapy; Antisocial Personality Disorder; Child; Child Behavior Disorders; prevention & control; Mental Disorders Diagnosed in Childhood; therapy